Students’ Voices: Poster Session as an Alternative Way of Teaching Writing - Amra Ariyani; Maemuna Muhayyang; Munir Munir; Geminastiti Sakkir (PT ARRUS Intelektual Indonesia, 2023)
This study aimed to investigate the students' participation and the student's perceptions of the use of poster sessions in essay writing classes. A qualitative method was applied in this study. The study respondents were third-semester English Education Study Program students who took an essay writing class. Sixty-third-semester students from two classes were selected randomly to participate in the study. The participants consisted of 30 students. The reason for choosing the third-semester students was that they have studied Paragraph Writing in the previous semester. In other words, they have basic writing skills. Data was collected using classroom observation notes and semi-structured interviews. The study indicated that students were comfortable, confident, and continuously engaged in learning essay writing. The result further revealed that all students showed positive perceptions of the use of poster sessions. They felt enjoyed and satisfied in learning essay writing by using poster sessions. They thought this was a new way to learn writing using poster sessions. They showed their interest in learning. They not only improved their skills in essay writing but also improved their oral skills. It was recommended that further researchers examine students' writing ability using poster sessions and identify other aspects that foster students` success in a poster session.